2003
DOI: 10.1152/japplphysiol.00983.2002
|View full text |Cite
|
Sign up to set email alerts
|

Maximal intermittent cycling exercise: effects of recovery duration and gender

Abstract: Billaut, Franç ois, Magali Giacomoni, and Guy Falgairette. Maximal intermittent cycling exercise: effects of recovery duration and gender. J Appl Physiol 95: 1632-1637, 2003. First published June 6, 2003 10.1152/ japplphysiol.00983.2002This study aimed to evaluate potential gender differences in recovery of power output during repeated all-out cycling exercise. Twenty men and thirteen women performed four series of two sprints (Sp1 and Sp2) of 8 s, separated by 15-, 30-, 60-, and 120-s recovery. Peak power (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
26
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 34 publications
8
26
1
Order By: Relevance
“…These results have implications in the context of multiple-sprint sports since short recovery periods, during short-term intermittent exercise, have been reported not only to decrease muscular performance (e.g., running speed), but also to negatively affect the quality of specific sporting skills (Ferrauti et al 2001). However, our results contrast with previous reports showing that a 30-s rest period is enough to restore power output for three or four consecutive 6-s sprints (Gaitanos et al 1993;Balson et al 1994b) or two 8-s sprints (Billaut et al 2003). These contrasting results may be linked to differences in initial (i.e., first sprint) power output, subjects' training status or to the different ergometers employed (Hunter and Enoka 2001;Bishop et al 2003;Bishop and Spencer 2004).…”
Section: Early Fatigue During Repeated Sprintscontrasting
confidence: 99%
“…These results have implications in the context of multiple-sprint sports since short recovery periods, during short-term intermittent exercise, have been reported not only to decrease muscular performance (e.g., running speed), but also to negatively affect the quality of specific sporting skills (Ferrauti et al 2001). However, our results contrast with previous reports showing that a 30-s rest period is enough to restore power output for three or four consecutive 6-s sprints (Gaitanos et al 1993;Balson et al 1994b) or two 8-s sprints (Billaut et al 2003). These contrasting results may be linked to differences in initial (i.e., first sprint) power output, subjects' training status or to the different ergometers employed (Hunter and Enoka 2001;Bishop et al 2003;Bishop and Spencer 2004).…”
Section: Early Fatigue During Repeated Sprintscontrasting
confidence: 99%
“…The present data were consistent with previous studies which observed no gender-related differences in CPP in pre-teenage individuals [5,6,29], whilst CPP was higher in males compared with females from about 13 years of age until adulthood [1,4,21,29,37,41]. In other words, boys, in contrast with girls, showed a clear adolescent growth spurt in leg muscle power.…”
Section: Cycling Peak Power (Watts) During Growthsupporting
confidence: 93%
“…For example, performance decrements during and across intermittent sprints (all-out sprints interspersed with rest periods long enough to allow near complete recovery of performance) are lower in women than in their male counterparts (Billaut et al 2003;Esbjörnsson-Liljedahl et al 1999, 2002Falgairette et al 2004). Similar observations have been made during repeated-sprint exercise (RSE; all-out sprints interspersed with brief recovery intervals) where women display a greater ability to maintain absolute peak power output, work and speed across sprint repetitions (Billaut and Smith 2009;Bishop et al 2003a;Laurent et al 2010;Yanagiya et al 2003).…”
Section: Introductionmentioning
confidence: 99%